Pengaruh Model Pembelajaran Joyfull Learning Dengan Strategi Everyone is a Teacher Here Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Biologi SMAN 26 Bone: (The Influence of The Joyfull Learning Model Using The Everyone is a Teacher Here Strategy on Student Learning Outcomes In Biology Subjects At SMAN 26 Bone) - Angga Andriana; Erwing Erwing; Romi Adiansyah (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
This research aims to see the influence of the Joyfull Learning Learning Model with the Everyone Is a Teacher Here Strategy on Student Learning Outcomes in Biology Subjects at SMAN 26 Bone. The type of research used in this research is pre-experimental research with a one group pre-test post-test design. This design uses two measurements of students regarding the material to be sampled. The results of this research indicate that the use of the Joyfull Learning Model with the Everyone Is a Teacher Here Strategy on Student Learning Outcomes in Biology Subjects at SMAN 26 Bone is effective. This can be seen in the level of students' abilities before using this learning model, namely the average was only 59.10. Furthermore, after using the Joyfull Learning Model with the Everyone Is a Teacher Here Strategy, the average score obtained was 85.35. This means that there has been an increase after implementing the Joyfull Learning Learning Model with the Everyone Is a Teacher Here Strategy. Based on the results of inferential statistical analysis using the t test formula, it can be seen that the t value is 13.686. With a frequency (dk) of 28-1=27, at a significance level of 5% obtained ttable 2.051. Thus, because the value of tcount > ttable at a significance level of 0.05, the use of the Joyfull Learning Learning Model with the Everyone Is a Teacher Here Strategy on Student Learning Outcomes in Biology Subjects at SMAN 26 Bone has an influence. Abstrak. Penelitian ini bertujuan untuk melihat Pengaruh Model Pembelajaran Joyfull Learning dengan Strategi Everyone Is a Teacher Here terhadap Hasil Belajar Siswa pada Mata Pelajaran Biologi SMAN 26 Bone. Jenis penelitian yang digunakan dalam penelitian ini adalah jenis penelitian pra-eksperimen dengan desain one group pre-test post-test design. Desain ini menggunakan dua kali pengukuran terhadap siswa tentang materi yang akan dijadikan sampel. Hasil penelitian ini menunjukkan bahwa penggunaan Model Pembelajaran Joyfull Learning dengan Strategi Everyone Is a Teacher Here terhadap Hasil Belajar Siswa pada Mata Pelajaran Biologi SMAN 26 Bone efektif. Hal ini dapat dilihat pada tingkat kemampuan siswa sebelum menggunakan model pembelajaran tersebut, yaitu rata-rata hanya mencapai 59,10. Selanjutnya setelah menggunakan Model Pembelajaran Joyfull Learning dengan Strategi Everyone Is a Teacher Here, nilai rata-rata yang diperoleh sebesar 85,35. Hal ini berarti terjadi peningkatan setelah diterapkannya Model Pembelajaran Joyfull Learning dengan Strategi Everyone Is a Teacher Here Berdasarkan hasil analisis statistik inferensial dengan menggunakan rumus uji t, dapat diketahui bahwa nilai thitung sebesar 13,686. Dengan frekuensi (dk) 28-1=27, pada taraf signifikansi 5% diperoleh ttabel 2,051. Dengan demikian, karena nilai thitung > ttabel pada taraf signifikansi 0,05, maka penggunaan Model Pembelajaran Joyfull Learning dengan Strategi Everyone Is a Teacher Here terhadap Hasil Belajar Siswa pada Mata Pelajaran Biologi SMAN 26 Bone memberikan pengaruh.